Wages and occupational flexibilities as determinants of the interactive QuBe labour market model : a methodlogical report on the basic projection of the 3rd wave of the BIBB-IAB qualifications and occupational field projections - Maier, Tobias [Verfasser]; Zika, Gerd [Verfasser]; Mönnig, Anke [Verfasser]; Wolter, Marc Ingo [Verfasser]; Kalinowski, Michael [Verfasser]; Hänisch, Carsten [Verfasser]; Helmrich, Robert [Verfasser]; Schandock, Manuel [Verfasser]; Neuber-Pohl, Caroline [Verfasser]; Bott, Peter [Verfasser]; Hummel, Markus [Verfasser] (My University, 2014)
The BIBB-IAB qualification and occupational field projections describe the labour demand and supply development until 2030. The BIBB-IAB.Qualification and Occupational Field Projections describe the labour demand and supply development until 2030. The discussion paper includes the underlying data, methods and assumptions of the third wave of the long-term BIBB-IAB Qualification and Occupational Field Projections (QuBeproject). Taken into account in the present third wave was the increased future net immigration as a consequence of the European economic crisis. In addition, empiricaly founded dynamic exchange processes between labour supply and demand by qualifications and occupation-specific labour supply in persons and hours is taken into account when determining wages for the respective occupations. On the supply side, the advantages of the two hitherto applied supply models BIBB-FIT and BIBB-DEMOS have been combined in one supply model and the wage elasticity coinciding with occupational flexibility has been estimated at the same time." (authors abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.2.1 Lohn- & Tarifsysteme; G 1.3.3.3 Mobilität; Arbeitsmarkt; Projektion; Arbeitskräfteangebot; Arbeitskräftebedarf; Qualifikation; Berufsfeld; Lohnentwicklung; Berufliche Flexibilität